Gene expression profiling in B-cell non-Hodgkin lymphomas - Renas N. Saleem; Ahmed Khudair Yassin (Iraqi Journal of Hematology)
BACKGROUND: Gene expression profiling has become a fundamental tool in cancer diagnosis and management. B-cell non-Hodgkin lymphoma (B-NHL) is a group of malignant neoplasms originating from the lymphoid tissues, mainly the lymph nodes and the gene expression technique was used to unravel its complexity and aid in clinical decision-making. OBJECTIVES: The aims of this study were to find the significance of gene expression profiling focusing on colony-stimulating factor 1 receptor (CSF1R), myeloid differentiation factor 88 (MyD88), and tumor necrosis factor-α (TNF-α) as a promising approach in B-NHL diagnosis and their comparison with healthy controls. PATIENTS, MATERIALS AND METHODS: The current clinical prospective study was mediated from June 1, 2021, to December 30, 2022, of NHL patients in Kurdistan, Iraq. Seventy-three patients were recruited from Nanakali Hospital for Blood Diseases and Cancer, Erbil. The integration of gene expression biomarkers uses quantitative real-time polymerase chain reaction technique to diagnose B-NHL. Specifically, we focused on three key genes MyD88, TNF, and CSF1R whose expression profiles were analyzed in B-NHL patients and controls. We leveraged a dataset to explore gene expression patterns in B-NHL and applied classification algorithms to distinguish between B-NHL patients and controls. RESULTS: The initial results show the overall lower CSF1R expression in B-NHL as compared to the controls and a significant reduction in CSF1R expression in females (≤50 years and >50 years). The result considers lower CSF1R expression in B-NHL males (≤50 years) and higher but not significant in males (>50 years). CONCLUSIONS: These B-NHL-expressed genes may be considered potential diagnostic markers with their meaningful comparisons to control groups, and they could be proposed to guide the management of patients and facilitate their stratification into clinical trials.